Coal Energy and Macroeconomic Conditions - Utomo, Selamet Joko; Mayvani, Titov Chuk’s; Imron, Mochamad Ali (International Journal of Energy Economics and Policy, 2021)
This paper assesses the effect of coal energy production volume, exchange rate, inflation and gross domestic product on the volume of Indonesia’s coal energy exports in 1998-2019. Based on an Autoregressive Distributed Lag (ARDL) approach, in the short run, we find that the coal energy production volume, exchange rate, and gross domestic product has a negative relationship to Indonesia’s coal energy exports. However, on the other hand, inflation has a positive relationship to Indonesia’s coal energy exports. In the long run, we also find that the coal energy production volume, inflation, and gross domestic product has a positive relationship to Indonesia’s coal energy exports. Besides, the exchange rate has a negative relationship to Indonesia’s coal energy exports. Keywords: Coal Energy, Exchange Rate, Inflation, Gross Domestic Product, Autoregressive Distributed Lag JEL Classifications: E2, E6, Q4, Q2 DOI: https://doi.org/10.32479/ijeep.11214